2020
DOI: 10.1093/gerona/glaa149
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Crosstalk With the Hallmarks of Aging

Abstract: Within the past several decades, the emergence of new viral diseases with severe health complications and mortality is evidence of an age-dependent, compromised bodily response to abrupt stress with concomitantly reduced immunity. The new severe acute respiratory syndrome coronavirus 2, SARS-CoV-2, causes coronavirus disease 2019 (COVID-19). It has increased morbidity and mortality in persons with underlying chronic diseases and those with a compromised immune system regardless of age and in older adults who a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 99 publications
2
62
0
4
Order By: Relevance
“…Typical common intracellular microbes with readily available serologic testing and Since long-term mortality data of Covid- 19 are not yet available, this prompted us to investigate whether sex differences in mortality would apply to other common infections. We tested associations between immunoglobulin G (IgG) antibody titers for HSV-1, HSV-2, CMV, C. pneumoniae, M. pneumonia and H. pylori and long-term mortality among persons aged ≥75 years, a group of people who are especially vulnerable to Covid-19 through numerous pathophysiological mechanisms related to ageing [11]. Besides being old and past reproductive age, our study subjects were community-dwelling and had a history of cardiovascular disease (CVD), which reduces the possibility that gender-patterned factors related to environment, lifestyle, current hormonal, and cardiovascular status would explain the findings.…”
Section: Introductionmentioning
confidence: 99%
“…Typical common intracellular microbes with readily available serologic testing and Since long-term mortality data of Covid- 19 are not yet available, this prompted us to investigate whether sex differences in mortality would apply to other common infections. We tested associations between immunoglobulin G (IgG) antibody titers for HSV-1, HSV-2, CMV, C. pneumoniae, M. pneumonia and H. pylori and long-term mortality among persons aged ≥75 years, a group of people who are especially vulnerable to Covid-19 through numerous pathophysiological mechanisms related to ageing [11]. Besides being old and past reproductive age, our study subjects were community-dwelling and had a history of cardiovascular disease (CVD), which reduces the possibility that gender-patterned factors related to environment, lifestyle, current hormonal, and cardiovascular status would explain the findings.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 show significant host factors for replication which are impacted by age coupled with comorbidities and immune system responses that enhance the severity of the viral infection. 16 Hence, it has been observed that the alveolar lesions occur in a variety of forms such as exudative inflammation, carnification, interstitial inflammation, fibrosis as well as focal hemorrhage. 17 Our study showed that deaths due to COVID-19 occurred in patients aged ≥60years.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection is associated with increased morbidity and mortality in individuals with underlying chronic diseases or a compromised immune system [225][226][227][228]. Groups of increased risk are men, pregnant and postpartum women, and individuals with high occupational viral exposure [229][230][231].…”
Section: Susceptibility Features Of the Hostmentioning
confidence: 99%
“…Importantly, age is one of the key aspects contributing to the severity of the disease. The elderly are at high risk of developing severe or critical disease [227,247]. Age-related elevated levels of pro-inflammatory cytokines (inflammation) [247][248][249][250], immunosenescence and cellular stress of ageing cells [125,227,247,251,252] may contribute to the risk.…”
Section: Susceptibility Features Of the Hostmentioning
confidence: 99%
See 1 more Smart Citation